2018
DOI: 10.1016/j.neuroimage.2017.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth leads to hyper-reactive cognitive control processing and poor white matter organization in adulthood

Abstract: Individuals born preterm with very low birth weight (VLBW; birth weight ≤ 1500 g) are at high risk for perinatal brain injuries and deviant brain development, leading to increased chances of later cognitive, emotional, and behavioral problems. Here we investigated the neuronal underpinnings of both reactive and proactive cognitive control processes in adults with VLBW. We included 32 adults born preterm with VLBW (before 37th week of gestation) and 32 term-born controls (birth weight ≥10th percentile for gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…Due to the challenges in obtaining reliable functional outcomes in neonates, DTI has emerged as an imaging biomarker for perinatal brain injury ( Vollmer et al, 2017 ; Hollund et al, 2018 ; Olsen et al, 2018 ). In particular, congenital hydrocephalus in children is associated with widespread DTI microstructural abnormalities ( Mangano et al, 2016 ; Zhao et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the challenges in obtaining reliable functional outcomes in neonates, DTI has emerged as an imaging biomarker for perinatal brain injury ( Vollmer et al, 2017 ; Hollund et al, 2018 ; Olsen et al, 2018 ). In particular, congenital hydrocephalus in children is associated with widespread DTI microstructural abnormalities ( Mangano et al, 2016 ; Zhao et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The preterm behavioral phenotype has been described as anxious and inattentive, rather than hyperactive or disruptive, which may also mean that their cognitive difficulties may not be as readily visible in a classroom setting 20 , 118 , 119 . Promisingly, working memory training interventions have shown learning gains in preterm-born preschoolers and adolescents 120 , 121 .…”
Section: Discussionmentioning
confidence: 99%
“…These limbic-cortical pathways are not only involved in socio-emotional behavior but also play a pivotal role in higher-order behavioral control. Studies repeatedly reported significant alterations in white matter microstructure, including the cingulum (i.e., connection between anterior cingulate cortex, dorsolateral prefrontal cortex, and inferior parietal lobe), fronto-occipital fascicles (i.e., bridging frontal-temporalparietal-occipital lobe), fornix, corpus callosum, and superior longitudinal fasciculus, amongst others (153,(251)(252)(253)(254)(255). These white matter indices have been directly linked to alterations in executive functioning, that is, lower executive functioning was related to reductions in several white matter microstructure (e.g., inferior-fronto-occipital fascicles, cingulum, and superior longitudinal fasciculus) [Wisconsin Card Sorting Test (256); Test of Everyday Attention for Children (TEA-Ch) (257); Child Behavior Check List (CBCL) (153); Delis-Kaplan Executive Function Systems (D-KEFS) (258)].…”
Section: Emotion Processing and Executive Functioningmentioning
confidence: 99%
“…More recent studies disentangled the neural underpinnings of proactive vs. reactive cognitive control in preterm-born adults. Using the Not-X continuous performance test (CPT), authors reported (1) hypo-activation between the frontal pole and anterior cingulate gyrus, as well as the posterior cingulate gyrus and precuneus, and (2) hyper-activation between the posterior cingulate gyrus and precuneus, and the right lateral occipital cortex and angular gyrus (255). In other words, authors showed that preterm born adults exhibited more reactive behavioral control, rather than proactive.…”
Section: Emotion Processing and Executive Functioningmentioning
confidence: 99%